Optimized gating and reference ranges of reticulated platelets in dogs for the Sysmex XT-2000iV - Oellers, Dana E.; Bauer, Natali; Ginder, Melanie; Johannes, Sigrid; Pernecker, Iris; Moritz, Andreas; Justus Liebig University Giessen (My University, 2016)
Background: Canine reticulated platelets (r-PLTs) i.e., juvenile PLTs reflecting thrombopoiesis can be measured automatically with the hematology analyzer Sysmex XT-2000iV using manual gating options. However, the impact of interferences on r-PLT measurements performed with the gates published previously (Pankraz et al., Vet Clin Path 38:30 38, 2009; Gelain et al., High fluorescent platelets fraction in macrothrombocytopenic Norfolk terrier, 2010) is largely unknown. The aim was to compare different published gates for measurement of r-PLTs with the Sysmex XT-2000iV with an own, optimized gate ( Oellers-gate ) and to establish reference intervals (RIs) in>120 dogs. Data of 362 measurements of diseased and healthy dogs were analyzed retrospectively. Several gates were applied and RIs for r-PLTs and platelet indices were established for pet dogs and a group of 153 healthy Beagles kept under defined housing conditions. Intra-assay precision (CV) was also assessed. Results: In 30/362 samples, interferences consistent with small erythrocytes/reticulocytes were seen in the previously published gates but not in the Oellers-gate . Good correlation was found between the different gates (rs: 0.88 1.00). RIs for the Pankraz-gate , the Gelain-gate , and the Oellers-gate were 0.0 1.2, 0.2 3.7 and 0.2 3.9 % respectively. CVs were ranging between 22 and 41 %. Conclusions: Optimization of previously published gates minimized interferences of small erythrocytes with r-PLT measurements.
Keywords: RNA-rich platelets; Canine; Hematology analyzer; ddc:630